Obstacles To The Implementation Of Active Learning Strategies From The Point Of View Of Teachers Of The First Cycle Of Basic Education (A Field Study In Tartous City) - غانم . ثناء; مبيض مهند; عمران ديما (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of this research was to identify the obstacles to the implementation of active learning strategies from the perspective of teachers of the first cycle of basic education in Tartous city, as well as explore whether there are statistically significant differences between the average scores of teachers. The sample of the study consisted of (350) teachers in Tartous city. The researcher has prepared a questionnaire on the obstacles to the application of active learning strategies consisting of (29) items, and distributed on four axes are obstacles related to (teacher, pupils, school curriculum, school environment), the researcher followed descriptive approach to achieve the objectives of the research, and Search reached for several results: -Most of the obstacles facing teachers in the implementation of active learning strategies are those related to the teacher, then the obstacles that relate to the students, then the obstacles that relate to the school environment, and then the obstacles that relate to the school curriculum. - There are differences between the average scores of teachers on the questionnaire on the obstacles to the application of active learning strategies according to the variable years of experience in favor of teachers who have years of experience more than 10 years - There are differences between the teachers’ average scores on the questionnaire on the obstacles to the application of active learning strategies according to the type of school variable for the benefit of public schools.